Connection Of Rhythmic And Choreography Lessons With Part 5 Of The Circle Lesson - Munisa Gayrulbekkizi Fatkhullaeva (Euro Asian Journal Publishing, 2024)
the article talks about a way to combine rhythm and choreography lessons with the 5th part of the tambourine lesson.
Keywords: improvisation; music; artistic; movement